Eksplorasi Makna Dan Nilai Sosial Pada Perilaku Konsumen Non Muslim Dalam Berburu Takjil Di Bulan Ramadhan : Studi Kasus Di Kota Medan - Dewi Nuriani Balqissyah; Debi Ester Claudia Siregar; Amnah Khairani; Azizah Heriyani Erizal; Cici Paranita Sipangkar; Serina Br Sembiring; GloriaWiryajaya; Wisnu Rayhan Adhitya (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This research explores the meaning and social value of non-Muslim consumer behavior in hunting takjil during Ramadan in Medan City. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results collected amounted to 35 sets (Respondents) from 7 different locations where the results showed that non-Muslim consumers showed tolerance, openness, and mutual respect for Muslims. They participate in Ramadan traditions and understand the associated social values. Factors that encourage non-Muslims to hunt for takjil include culinary curiosity, the vibrant atmosphere of Ramadan, and support from Muslims. Takjil hunting also reflects the values of tolerance, togetherness and sharing. The month of Ramadan brings changes in the consumption habits of non-Muslims, with positive impacts in social and economic aspects.